Recovery of Methicillin Resistant Staphylococci from Public Vehicles in Kathmandu (Tribhuvan University Journal of Microbiology, 2023)
Objectives: The purpose of this study was to determine the extent of staphylococcal contamination in public vehicles in Kathmandu and to determine the antibiotic susceptibility pattern of the isolates.Methods: This cross-sectional study was conducted from December 2022 to May 2023 in the Microbiological laboratory of Padma Kanya Multiple Campus, Kathmandu. A total of 120 swab (sterile cotton swab moistened with sterile normal saline) samples were collected by gently rubbing the surfaces from 19 different micro-buses during the time of heavy passenger flow (office time) and transported to the laboratory maintaining a cold chain. Staphylococcus aureus and Coagulase negative Staphylococci (CoNS) were identified by their characteristic yellow pigmented colonies on Mannitol Salt Agar (MSA) and the ability of S. aureus to produce coagulase enzyme. Kirby-Bauer disc diffusion method was employed to test the antibiotic susceptibility pattern of isolates. MRSA were identified on the basis of the zone of inhibition (